Influence of cold drawing deformation and annealing temperature on microstructure and tensile properties of Al-Si-Sc-Zr alloy wires - ZHENG Tao; SHI Hanchao; CHEN Bingqing; XIONG Huaping (Cailiao gongcheng)
The effect of different cold drawing deformations and annealing temperatures on the microstructure and tensile properties of Al-Si-Sc-Zr alloy wires is investigated by the mean of electron backscatter diffraction technique. The results show that the grains are elongated and refined along the drawing direction， accompanying with the fibrous structure and a typical〈111〉deformation texture with strain increasing. However， when the drawing strain increases from 0.61 to 0.76， the average grain size increases and the proportion of low-angle grain boundaries decreases due to the recrystallization behavior in the grains. Furthermore， the tensile strength and yield strength of the wire increase to 181.5 MPa and 166.5 MPa， respectively， due to the work hardening induced by the cold drawing process. When the cold-drawn wires are subjected to the annealing treatment at 350-450 ℃ for 2 h，the fibrous cold-drawn structure is transformed into fine equiaxed grains， and the typical cube texture ｛100｝〈001〉 is formed. This annealing treatment can significantly eliminate the work hardening caused by the cold drawing. In this case， the yield strength decreases from 166.5 MPa to 84.0 MPa， meanwhile the elongation after fracture increases from 2.1% to 9.5%. The annealed structure is uniform and stable， which is favorable to subsequent cold drawing processes.